Stereoselective 11C Labeling of a "Native" Tetrapeptide by Using Asymmetric Phase‐Transfer Catalyzed Alkylation Reactions. Issue 5 (9th February 2017) - Pekošak, Aleksandra; Rotstein, Benjamin H.; Collier, Thomas L.; Windhorst, Albert D.; Vasdev, Neil; Poot, Alex J.
Abstract : The first 11 C‐labeled unmodified ("native") peptide is described by alkylation of a tetrapeptide Schiff base, which was achieved by an automated five‐step radiochemical reaction. In a proof‐of‐concept study, [ 11 C]Phe‐d ‐Trp‐Lys‐Thr was synthesized. This tetrapeptide is the essential pharmacophore of octreotide, an antagonist of somatostatin receptors. The asymmetric alkylation with chiral phase‐transfer catalysts enabled direct labeling of a variety of isolated 11 C‐peptides in a highly stereoselective manner (94 % de ) with acceptable radiochemical yields (9–10 %) and practical specific activities (15–35 GBq µmol –1 or 405–945 mCi µmol –1 ) at the end of synthesis. This novel methodology provides a powerful new radiosynthetic method to access novel, stereochemically pure carbon‐11‐labeled native small peptides ready for in vivo studies. Abstract : Phase‐transfer catalysis now allows asymmetric multistep carbon‐11 peptide radiolabeling. The 11 C–C bond formation proceeds with high radiochemical conversions and high levels of diastereoselectivity. The optimal use of chiral phase‐transfer catalysis furnishes unprecedented native, that is, unmodified, 11 C‐labeled peptides for positron emission tomography imaging.